1982
DOI: 10.1002/1097-0142(19820215)49:4<722::aid-cncr2820490421>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Tumor markers in inclusion cysts of the ovary

Abstract: The immunoperoxidase method was used to determine whether carcinoembryonic antigen, beta subunit of HCC placental lactogen, pregnancy-associated alpha-2 glycoprotein, and pregnancy-specific beta-1 glycoprotein could be found in inclusion cysts of the ovary. These tumor markers are found in the serum of patients with common epithelial carcinomas of the ovary and inclusion cysts are considered to be the origin of these tumors. Placental lactogen was found in 56 of 118 inclusion cysts, beta subunit of HCG in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The general pattern of low expression in ovarian surface epithelium and higher expression in inclusion cysts seen in our study has been previously reported in other studies [9]. It is thought that high hormone levels in the ovarian stroma may induce expression of a range of genes in the epithelium lining inclusion cysts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The general pattern of low expression in ovarian surface epithelium and higher expression in inclusion cysts seen in our study has been previously reported in other studies [9]. It is thought that high hormone levels in the ovarian stroma may induce expression of a range of genes in the epithelium lining inclusion cysts.…”
Section: Discussionsupporting
confidence: 89%
“…Although it is widely believed that serous ovarian cancers arise from the ovarian surface epithelium and inclusion cysts formed when ovarian surface epithelium become trapped inside the ovary [9], a more recent hypothesis for the initiation of ovarian cancer suggests that precursor lesions exist in the fimbriated end of the fallopian tube epithelium [10]. It is possible that fallopian tube epithelium become trapped within the ovarian stroma during healing of the ovulatory wound where the high hormonal milieu may cause malignant transformation in a manner akin to the hypothesis for inclusion cysts [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely believed that some or all of these arise from precursors originating from the ovarian surface epithelium, via inclusion cysts or serous benign and borderline tumors (5)(6)(7)(8). Obvious candidate precursors are serous ovarian cystadenomas and cystadenofibromas, which are benign lesions with a cystic mass of 1 cm or more in diameter, lined with a single layer of cuboidal to columnar epithelium and commonly associated with a fibromatous stromal mass ( Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cells lining cysts lose their original shape with the expansion of the cysts. There are few reports of immunostaining to distinguish a kind of ovarian cyst in other animals [2,9]. In the present study, we immunohistochemically examined 109 ovarian cysts, including cysts of SES, graafian follicle cysts, cystic rete ovarii and histologically unclassified cysts in dogs.…”
mentioning
confidence: 97%